DETERMINAN KEPATUHAN IBU HAMIL MENERAPKAN PROTOKOL PENCEGAHAN COVID-19 DI PUSKESMAS KELURAHAN PETOJO SELATAN TAHUN 2021 - Sri Lestari; Sarah Handayani; Rustika, Rustika (Jurnal Cakrawala Ilmiah, 2023)
The COVID-19 outbreak affects everyone regardless of age or gender, including pregnant women. The number of pregnant women infected with COVID-19 in Indonesia as of December 1, 2020 is 148 people. Based on monitoring data in the Gambir District Health Center, Central Jakarta in September - December 2020 there were (6.73%) pregnant women who were positively infected with COVID-19 then (5%) of them died and (10%) babies died. The number of pregnant women infected with COVID-19 at the Petojo Selatan Village Health Center in early September - December 2020 was 11% people. The purpose of this study was to find out the factors related to the compliance of pregnant women in applying the COVID-19 prevention protocol at the Petojo Selatan Sub-district Health Center in 2021. The design of this study was quantitative with cross sectional method and equipped with qualitative. The study was conducted in September - May 2021. Data collection was carried out in April 2021. The respondents of this study consisted of all pregnant women who had their pregnancy checked in September 2020 - April 2021 as many as 150 people. There were 50 respondents who entered the exclusion criteria and 100 people who entered the inclusion criteria. Techniques of data analysis using statistical software which includes univariate, bivariate and multivariate analysis. The bivariate results showed that there was a significant relationship between pregnant women's adherence to the COVID-19 prevention protocol with education (P-value 0.023), perceived benefits (P-value 0.025), and perceived barriers (P-value 0.013). The results of the multivariate test showed that there was 1 variable that was significantly related (dominant) to the compliance of pregnant women, namely perceived barriers (P-Value 0.008) with PR 3.059. The results of the qualitative analysis show that perceived barriers are the main factors that hinder the compliance of pregnant women in implementing the COVID-19 prevention protocol. The recommended effort to overcome the magnitude of the obstacles in implementing the COVID-19 prevention protocol for pregnant women is to increase the awareness of pregnant women about the importance of implementing the COVID-19 prevention protocol, in this case the support of husbands, families, communities and health workers is needed. The public is expected to be more sensitive to health information and knowledge, especially the COVID-19 prevention protocol. In addition, the community health center is expected to increase health promotion efforts related to the COVID-19 prevention protocol in the community by forging partnerships with cross-sectors.